PENERAPAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN SKI UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI MTsN 4 PIDIE - Bukhari; Nasri Diana (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
The purpose of this study was to determine the application of audio-visual media to improve student learning outcomes in SKI learning at MTsN 4 Pidie. This research was conducted using a descriptive qualitative research method in the form of a case study research method. The research instrument used was a closed questionnaire which consisted of 15 multiple choice questions. The population in this study was class VIII, which consisted of 276 students, with details of 121 male students and 155 female students and 2 SKI teachers at MTsN 4 Pidie. The samples in this study were: 2 SKI teachers, and 20% of the total number of Grade VIII students, which consisted of 55 students. VIII-1 as many as 28 students wich are 11 male students and 17 female students and class VIII-2 students as many as 27 students wich are 10 male students and 17 female students. The results showed that there was an effect of the application of audio-visual media in SKI learning on student learning outcomes at MTsN 4 Pidie. As many as 39 students answered satisfactorily which is 70.9%.